2017
DOI: 10.1073/pnas.1707506114
|View full text |Cite
|
Sign up to set email alerts
|

Near-atomic structure of jasplakinolide-stabilized malaria parasite F-actin reveals the structural basis of filament instability

Abstract: During their life cycle, apicomplexan parasites, such as the malaria parasite , use actomyosin-driven gliding motility to move and invade host cells. For this process, actin filament length and stability are temporally and spatially controlled. In contrast to canonical actin, actin 1 (Act1) does not readily polymerize into long, stable filaments. The structural basis of filament instability, which plays a pivotal role in host cell invasion, and thus infectivity, is poorly understood, largely because high-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
140
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(155 citation statements)
references
References 64 publications
(91 reference statements)
11
140
1
Order By: Relevance
“…The structure and binding site of JASP is the same in all of our different cryo-EM structures of 206 F-actin complexed with JASP Pospich et al, 2017) (Figure 6,. Its binding site overlaps to a large proportion with the one of phalloidin, as illustrated by a 208 superposition of structures ( Figure S3D-F).…”
Section: Comparison Of Phalloidin and Jasp Binding To F-actin 205mentioning
confidence: 64%
See 2 more Smart Citations
“…The structure and binding site of JASP is the same in all of our different cryo-EM structures of 206 F-actin complexed with JASP Pospich et al, 2017) (Figure 6,. Its binding site overlaps to a large proportion with the one of phalloidin, as illustrated by a 208 superposition of structures ( Figure S3D-F).…”
Section: Comparison Of Phalloidin and Jasp Binding To F-actin 205mentioning
confidence: 64%
“…First experiments using X-ray fiber diffraction, mutational studies, scanning 87 transmission electron microscopy or computational docking (Belmont et al, 1999a;Drubin et 88 al., 1993;Lorenz et al, 1993;Oda et al, 2005;Steinmetz et al, 1998), identified the binding 89 site of phalloidin at the interface of three actin protomers, but failed to determine its exact 90 position within the filament. Only recent high-resolution electron cryo microscopy (cryo-EM) 91 studies revealed the exact interaction of phalloidin and JASP with F-actin (Iwamoto et al, 2018;92 Mentes et al, 2018;Pospich et al, 2017). Both toxins bind non-covalently 93 to the same site consisting of three actin subunits from both strands and stabilize the filament 94 by extensive hydrophobic interactions.…”
Section: Introduction 34mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we solved the structure of the non-canonical actin filaments of Plasmodium falciparum , the parasitic microorganism causing malaria, in complex with the naturally occurring cyclic peptide jasplakinolide, exemplifying the potential of cryo-EM for structure-based drug design (Fig. 2b) [55]. We identified that subtle but significant differences are responsible for the inherent instability of the filaments, which is an essential feature for proper host cell invasion of the pathogen.…”
Section: Single-particle Cryo-em Of Biomedically Relevant Proteinsmentioning
confidence: 99%
“…In vitro , apicomplexan actins tend to form only short filaments of ~100 nm without the filament-stabilizing macrolide jasplakinolide 79,11 . T. gondii actin (TgAct) has been proposed to follow an isodesmic polymerization mechanism 10 , which would differ fundamentally from the classical nucleation-elongation pathway.…”
mentioning
confidence: 99%